Faktor-Faktor yang Berhubungan dengan Beban Kerja pada Unit Produksi di PT Summit Adyawinsa Indonesia Tahun 2025 - Rifqy Harits Munadil; Decy Situngkir; Ira Marti Ayu; Putri Handayani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
The Preliminary study results indicate that 7 out of 10, or around 70% of production workers at PT Summi Adyawinsa Indonesia experienced a high workload. This research employed a quantitative descriptive method with a cross sectional study design. The sample consisted of 132 workers, selected using a non-probability sampling technique. The study was conducted from June to July 2025. Data were analyzed using univariate analysis and bivariate analysis with the chi-square test. Primary data were collected through questionnaires as the research instrument. The univariate results showed the highest proportions was hish workload (93,9%), long working hours (65,9%), short work period (66,7%), productive age (93,2%), male gender (93,9%), high wages (53%), and good work environment (94,7%). Bivariate results show a relationship between working hours (p value 0,019), and work period (p value 0,05) with workload. There is no association between age (p value 1,000), gender (p value 0,402), wages (p value 0,147), and work environment (p value 1,000) with workload. Workload Companies need to increase the number of employess, perform routine maintenance on machinery and heavy equipment (forklifts and hoist cranes), and provide training for both new and existing workers.